Microfluidic flow and heat transfer and their influence upon optical modes in microstructure fibres - Davies, Edward M.; Christodoulides, Paul; Florides, Georgios A.; Kalli, Kyriacos (My University, 2015)
Downloading of the abstract is permitted for personal use only.Using finite element analysis (FEA), a model has been constructed to predict the thermo-fluidic and optical properties of a microstructure optical fibre (MOF). The properties under study include external temperature, input water velocity and optical fibre geometry. Under laminar flow the steady-state temperature is dependent on the water channel radius while independent of the input velocity. A critical channel radius is observed below which the steady-state temperature of the water channel is constant, while above, the temperature decreases. The MOF has been found capable of supporting multiple modes whose response to temperature was dominated by the thermo-optic coefficient of glaß, despite the larger thermo-optic coefficient of water. This is attributed to the majority of the light being confined within the glaß, which increased with increasing external temperature due to a larger difference in the refractive index between the glaß core and the water channel.
Keywords: FEA; Microfluidics; Mode analysis; Optical fibre; Thermofluidic